Connecting Glass-Forming Fragility to Network Topology - Sidebottom, David L. (Frontiers in Materials, 2019)
Glass fragility is a byproduct of early attempts to apply law of corresponding states scaling to the temperature dependent thickening of glass forming liquids. Efforts to plot the logarithm of the viscosity versus inverse temperature scaled to the glass transition point (T_g) fail to collapse data to a common, universal curve but instead display an informative pattern: at one extreme, many "strong" oxide glasses exhibit a single Arrhenius dependence, and at the other extreme, many "fragile" molecular liquids display a highly non-Arrhenius pattern in which the viscosity increases far more rapidly just in advance of T_g. In this regard, network-forming glasses composed of 3D networks of covalently bonded atoms are of interest as they undergo systematic changes in both T_g and fragility depending on the topology of the network and display variations of the fragility index spanning from strong (m ≈ 17) to fragile (m ≈ 90) depending on the level of network connectivity. Here we review the merits of a special, coarse-grained definition for the topological connectivity of network-forming glasses that differs from conventional constraint-counting approaches but which allows the fragility of over 150 different network-forming glasses (both oxides and chalcogenides) to be collapsed onto a single function of the average network connectivity. We also speculate on what role this coarse-grained connectivity might play in determining the glass transition temperature.